A Case of Intra - Abdominal Extralobar Pulmonary Sequestration: Prenatal Detection, Postnatal Diagnostic Approach and Outcome - Derya Eroğlu; Nurper Önder Denizoğlu; Orkan Ergün (Gynecology Obstetrics & Reproductive Medicine, 2017)
This paper describes the perinatal and postnatal outcome of a case considered to have a fetal intra-abdominal extralobar pulmonary sequestration (ELS). Routine midtrimester fetal ultrasonographic scan detected an abdominal echogenic mass between aorta and stomach. It was considered primarily as an intra-abdominal ELS. At postnatal 2 months, computed tomography (CT) scan with intravenous contrast described it as an ELS at the level of diaphragmatic hiatus by showing the aberrant blood supply to the sequestration with venous drainage into the portal confluence. The patient is now 4 years old and asymptomatic; she is being followed-up by a pediatric surgeon. Intra-abdominal ELSs usually remain asymptomatic throughout life; they may be safely observed without surgery unless they become symptomatic or show any change in the characteristics of the radiologic appearance.